FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA OPERASIONAL LEMBAGA PERKREDITAN DESA (LPD) KABUPATEN BADUNG - I Putu Adi Widiyana; Komang Krishna Yogantara; Made Christin Dwitrayani (Journal Research of Accounting, 2020)
Lembaga Perkreditan Desa (LPD) is currently in the public spotlight following the bankruptcy of Lembaga Perkreditan Desa (LPD) in Badung Regency from 2015 to 2017. The purpose of this study was to determine the effect of productive asset growth (loans), third party funds (growth in savings and deposits), and number of customers (customers of credit, savings and deposits). The sample in this study was 62 Lembaga Perkreditan Desa (LPD). Determination of the sample using purposive sampling method. The results of this study indicate that the variable earning assets (credit provided) have an effect on operational performance (BOPO) which is indicated by a significance value of 0.004. Third party fund variables (savings) have an effect on operational performance (BOPO) which is indicated by a significance value of 0.007. Variables of third party funds (deposits) have an effect on operational performance (BOPO) indicated by a significance value of 0,000. The variable number of credit customers has an effect on operational performance (BOPO) which is indicated by a significance value of 0.023. The variable number of savings customers has an effect on operational performance (BOPO) which is indicated by a significance value of 0.006. Likewise, the variable number of deposit customers has an effect on operational performance (BOPO) which is indicated by a significance value of 0.005. Simultaneous testing results prove that the variable growth in earning assets (loans), third party funds (growth in savings and deposits) and the number of customers (customers of credit, savings, and deposits) together influence the operational performance of Village Credit Institutions (ratio BOPO) in Badung Regency.Keywords: credit, savings, deposits, customers, performance.